Customer’s perception towards Petronas lubricant products in Bintulu District / Noorudin Haili - Haili, Noorudin (2006)
Motor vehicle lubricant business is a very competitive in Malaysia. There are a lot of players in the marketplace. The major players are Shell, Exxon Mobil, PETRONAS and Castrol. In 2005, PETRONAS lubricant products market share stood at 14%. This paper will study customer’s perception towards PETRONAS lubricant products in Bintulu district. The variables that will be studied are price, advertisement and sales promotion of the products. From the study, it is concluded that the price of the products as compared against quality and competitors price are well perceived by the customers. However, PETRONAS advertisement and sales promotion are not well perceived by the customers.